A single‐ and multiple‐dose study to investigate the pharmacokinetics of epelsiban and its metabolite, GSK2395448, in healthy female volunteers. Issue 6 (26th August 2015) - Mahar, Kelly M.; Stier, Brendt; Fries, Michael; McCallum, Stewart W.
Abstract: An open‐label single‐ and repeat‐dose study was conducted to investigate the pharmacokinetics, safety, and tolerability of ascending doses of epelsiban in healthy female volunteers (n = 48). The pharmacokinetics of the epelsiban metabolite, GSK2395448, were also assessed. Epelsiban was readily absorbed and parent and metabolite readily appeared in plasma. The parent drug's median tmax was approximately 0.5 hours, and the metabolite's median tmax ranged from 0.5 to 1.0 hours post–parent dosing. Both epelsiban and GSK2395448 had rapid elimination half‐lives, ranging between 2.66 and 4.85 hours. The metabolite:parent ratios for exposure (AUC and Cmax ) ranged from approximately 70% to greater than 100%, and therefore, GSK2395448 is considered a major metabolite of epelsiban. Mean epelsiban and GSK2395448 AUC values increased in a dose‐proportional manner following both single‐dose administration from 10 to 200 mg and repeat administration from 10 to 150 mg following twice daily or 4‐times‐daily dosing. Single‐dose epelsiban pharmacokinetics in women was similar to single‐dose pharmacokinetics previously observed in men. Epelsiban was generally well tolerated, and no events of clinical concern were observed in volunteers dosed in this study. The safety findings were consistent with the previous study in men, with headache the most commonly reported adverse effect.